The Calculation of Expense Reduction based on the Efficiency of Cyclone by Computational Fluid Dynamic - Wahyudi, Dhany Eko; Nuraini, Syarifa; Dewi, Wulandari Kusuma; Aisyah, Retno Mardiyah; Septiani, Eka Lutfi (International Journal of Mechanical Engineering Technologies and Applications, 2021)
The rotary kiln in cement industries used hot air (temperature 14500C)Â  for doing a reaction to form a clinker. The outlet hot air from the combustion reaction in the kiln is reused to decrease the water content of coal in the coal mill. However, the hot air that contained ash will affect the drying process in the coal mills will not reach the maximum point. Therefore, the hot air needs treatment to separate the hot air and particle. The hot air is carried out to the cyclone. The goal of this study is to investigate the efficiency work of cyclones in cement industries using the CFD method. Besides, the other goal of this research will convey the expense that is reduced in decreasing the ash content in hot air. In general, the good cyclone has the low-pressure drop, the turbulence model using Reynold Average Navier Stokes (RANS) simulation,k-Îµ standard, with the Lagrangian model to solve the problem in particle lane. The result of this study is showing the pattern of the ash in cyclones,Â  the pressure in cyclones, and the efficiency of cyclones. The number of efficiencies will affect the reduction of expense in this section.